2019
DOI: 10.1590/s1678-3921.pab2019.v54.00434
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate fertilization with organomineral fertilizer on corn crops on a Rhodic Khandiudox with a high phosphorus contente

Abstract: The objective of this work was to evaluate the nutritional content and grain yield of three corn (Zea mays) crops in response to phosphate fertilization with an organomineral fertilizer based on poultry litter or a mineral fertilizer, when cultivated on a Rhodic Khandiudox with a high initial phosphorus content. The experiment was carried out in the field in a randomized complete block design in a 2×4+1 factorial arrangement (organomineral or mineral fertilizer × 20, 40, 60, or 80 kg ha-1 P + control treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…However, these benefits were not effective in increase grain yield (Figure 2), thus using OM fertilizers may be economically unfeasible. However, it is noteworthy that the treatments OM 100 and PL 100 presented higher values of AEI in the parameters SDMY and nutrient accumulation than FM 100, since these two add equivalent rates of N, P, and K. The presence of the organic component and micronutrients in the OM fertilizer and in the PL may bring some advantage to plant growth in comparison to strictly mineral fertilization (Grohskopf et al, 2019), but with no consequence in grain yield.…”
Section: Efficiency Indicesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, these benefits were not effective in increase grain yield (Figure 2), thus using OM fertilizers may be economically unfeasible. However, it is noteworthy that the treatments OM 100 and PL 100 presented higher values of AEI in the parameters SDMY and nutrient accumulation than FM 100, since these two add equivalent rates of N, P, and K. The presence of the organic component and micronutrients in the OM fertilizer and in the PL may bring some advantage to plant growth in comparison to strictly mineral fertilization (Grohskopf et al, 2019), but with no consequence in grain yield.…”
Section: Efficiency Indicesmentioning
confidence: 92%
“…Dashed line represents AEI of 100% present in MF may result in greater efficiency of OM fertilizers (Antille et al, 2014;Borges et al, 2019). In addition, the presence of the organic fraction could reduce the solubility of the fertilizer, resulting in a more gradual release of nutrients into the soil (Grohskopf et al, 2019;Mumbach et al, 2019). However, these benefits were not effective in increase grain yield (Figure 2), thus using OM fertilizers may be economically unfeasible.…”
Section: Efficiency Indicesmentioning
confidence: 99%
“…Caption: Mineral Fertilizer (MF) and Organic Fertilizer (OF) The increase in corn productivity was affected by the increase in the application of organic fertilizer in due points (OF5, OF4 and OF2 125, 100 and 25 kg ha -1 ) (Figure 5), while the best result presented in (Figure 6) was the use of mineral fertilizer at 200 kg ha -1 (MF2). Grohskopf et al (2019) using in one experiment two different fertilizers (mineral and organomineral), observed that when applying the organomineral the response in the release of phosphorus was higher in the soil.…”
Section: Agronomic Resultsmentioning
confidence: 99%
“…Figueiredo et al (2012) observou aumento da produtividade de milho utilizando adubação organomineral. Em solos com alto teor de fósforo, a aplicação de fertilizante organomineral resultou em um aumento de 20% na produtividade de milho em relação ao adubo mineral (Grohskopf et al, 2019). A adubação organomineral apresentou um de ganho de produtividade de soja de 17,31% em relação a adubação mineral, (Duarte et al, 2013).…”
Section: Vivênciasunclassified